TRANSIENT ISCHEMIC ATTACK AS AN ARTERIAL HYPERTENSION COMPLICATION - G. N. Gorochovskaya; A. P. Kondrachin; A. I. Martinov (Столичная издательская компания, 2015)
Data about relations between arterial hypertension, transient ischemic attacks (TIA) and strokes are presented. Pathophysiology, clinic and diagnosis of TIA are described. Possibilities of different classes of antihypertensive drugs to prevent cerebral blood flow disturbances are discussed. Other therapeutic and surgery approaches to the TIA therapy in hypertensive patients are considered.